Role of exosomes in castration-resistant prostate cancer - Cao, Yuan; Wang, Jianjun; Luo, Huiwen; Wang, Yaodong; Cai, Xianfu; Zhang, Tiansheng; Liao, Yougang; Wang, Decai (Frontiers in Oncology, 2025)
Prostate cancer (PCa) is one of the most common urological malignancies in older male patients. Castration-resistant prostate cancer (CRPC) is an aggressive and refractory stage of PCa and is the leading cause of PCa-related deaths. Exosomes are small spherical vesicles with a lipid bilayer membrane structure, secreted by cells, which carry large amounts of nucleic acids, proteins, lipids, and various important reactive small molecules. Numerous studies have demonstrated that exosomes are involved in the development of CRPC by delivering various biomolecules that regulate biological processes in recipient cells. Despite the advancement in treatments, CRPC remains poorly managed, underscoring the urgent need for novel treatment strategies.As research into exosomes continues, they have shown significant potential in the diagnosis and treatment of CRPC.Unlike previous reviews,this review not only provides an overview of exosomes but also comprehensively explores their role in the CRPC tumor microenvironment, angiogenesis, immune escape, metastasis, and drug resistance, with a focus on the potential value of exosomes in the diagnosis and treatment of CRPC.The literature review includes studies published up to June 2024, and the search strategy involved exosomes, CRPC, diagnosis,and treatment using Pubmed.